Systematic Review of Kangaroo Care Duration's Impact in Neonatal Intensive Care Units on Infant-Maternal Health - Clarke-Sather, Abigail R; Compton, Crystal; Roberts, Kari; Brearley, Ann; Wang, Sonya G (American journal of perinatology, 2024)
Kangaroo care (KC), skin-to-skin contact between infants and caregivers, is encouraged in neonatal intensive care units (NICUs) to support health through improved weight, growth, and infant-maternal attachment while reducing the incidence of sepsis and infant pain. However, the optimal duration and frequency of KC to maximize health outcomes is unknown. Given parents' time stressors, identifying optimal KC time is critical. A literature review was undertaken on May 28, 2021 via querying the PubMed database from January 1, 1995, to May 28, 2021, regarding KC and NICUs with 442 results. Eleven studies met the eligibility criteria of (1) comparative KC between infants and adult caregivers in NICUs as a randomized controlled trial, (2) peer-reviewed articles in English, (3) study subjects ≥5, (4) health outcomes, and (5) KC sessions >1. Infant physical growth parameters, infant neurodevelopment, infant stress via salivary cortisol levels, and breastfeeding outcomes appear to increase with KC as compared with standard care (SC) without KC. Improvements were observed with longer KC duration, 2 h/d as compared with 1 h/d, for neurodevelopment and breastfeeding outcomes, but no greater improvement with longer KC duration was shown for reducing infant stress through salivary cortisol levels. Regarding maternal stress, the influence of KC duration showed mixed Parental Stressor Score: NICU scores. Further study on the impact of KC duration and frequency on health outcomes and dose-response relationship would help determine how much and how frequent KC is needed to improve specific health outcomes for infants and their mothers. KEY POINTS: · Data on kangaroo care duration's health impacts is lacking.. · Establishing dose-response for kangaroo care is needed.. · Kangaroo care for longer improves some but not all outcomes..